Social Welfare Maximization in Smart Grid: Review. Issue 1 (March 2021) - Ramnath, Gaikwad Sachin; Harikrishnan, R.
Abstract: The modernized power grid system intelligently integrates various advanced Information and Communication Technologies (ICT's) with various renewable energy sources. Moreover, recently huge developments are happening in renewable sources, with enhancement in technologies eras, the role of consumers is shifting towards producers so-called "prosumers". Furthermore, main challenges are enlarged energy demands, uncertainty in weather conditions and varied occupant's behavioural interventions in energy consumption. So, residential user-end is having potential for energy optimization by energy efficiency, conservation, and active participation. Besides, the dynamic fair energy pricing with respect to generation cost and load demands is motivational parameters to users. On the same, this paper focuses on analysing a novel, attractive business model that can actively participate prosumers through dynamic pricing and incentive based demand response programs for the maximization of social welfare. Further this review paper focusses on various optimization models to achieve social welfare maximization. And also bibliometric analysis has been done through the Scopus database.